What Obama means ... for our culture, our politics, our future - Asim, Jabari (William Marrow, 2009)
Asim, author of the acclaimed "The N Word," provides the context needed to understand what the Obama presidency means to Americans of all backgrounds, showing how African American performers, athletes, rhetoricians, and leaders laid the groundwork for Obama and how Obama turned the old civil-rights model of African American leadership on its head.